(untitled) (Journal of Science and Technology, 2016)
In search for an alternative source of energy, various feedstocks and wastes are being investi-gated to identify their potential in methane generation through anaerobic digestion. The addition of cattle manure to the predominant substrate is reported to have positive effect on the co-fermentation process thereby improving the buffer capacity. The manure is also essential for the digestion in order to have a relatively stable process. The proportion of cattle manure in the mix substrate influences the stability of the anaerobic digestion process. In this study co-fermentation treatments with varying proportions of shea waste and cattle manure were investi-gated. It was found out that only the treatment with 50% by volume of cattle manure showed process stability, producing biogas with high methane content